PERKEMBANGAN DAN CIRI-CIRI PERKEMBANGAN PADA ANAK USIA DINI - Sriyanto, Agus; Sutrisno, Sutrisno (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2022)
Childhood is a golden age that must be passed by every human being, if the childhood age grows and develops well then the child will grow and develop maturely at the next age. Childhood age greatly determines the next stage of life, if the child's age has completed the developmental tasks, the child will continue to the next stage of development maturely without anything being lost in the child. Children who live in loving families and have their physical and psychological needs met are considered capable of carrying out their developmental tasks and are able to develop psychological aspects. Children are able to move to the next stage and are able to develop psychological aspects until they are at a later age, mature when they enter puberty, teenagers to adulthood which are full of life's challenges. At each stage of development there are developmental barriers. Obstacles in child development are still in normal conditions and do not interfere with child development. That is the concept of humans who have advantages and disadvantages as servants who continue to develop and change (change over time), who need to introspect themselves and develop themselves to become servants of God who are pious.